Who is in the picture? The gender composition of images of Congress in party caucus Twitter feeds and online media. (2nd October 2018) - Bos, Angela L.; van Doorn, Bas W.; Nelson, Kjersten
ABSTRACT: Visual portrayals of politics can affect public opinion. However, little work has investigated visual portrayals of Congress and their impact on perceptions of group representation. Though women are underrepresented in Congress, the political parties, driven by electoral incentives, might try to present themselves as more diverse than they really are. Is this true for gender, and do these efforts trickle down to images in media coverage? We examine images of Members of Congress (MoCs) from congressional party caucus Twitter feeds and images in online mass media to assess whether the gender composition within the images accurately portrays institutional and party compositions. We test a theory as to why women MoCs may be overrepresented in images tweeted by the political party caucuses, paying special attention to why the two parties' incentives differ and how incentives increase when communications focus on women's issues, especially for Democrats who "own" women's issues. Our analyses of tweeted images show that both party caucuses overrepresent women MoCs, particularly in communication about women's issues. In contrast, online mass media images accurately represent the percentage of women in general, though mass media overrepresent women MoCs from both parties in images accompanying stories about women's issues.